PROVISION OF GREEN SPACES IN MALAYSIAN PRIMARY SCHOOLS: ISSUES, GUIDELINES AND RECOMMENDATION - Aziz, Nor Fadzila; Said, Ismail (PLANNING MALAYSIA, 2018)
The provision of conducive learning environments in schools is important in determining the effectiveness of the curriculum and co-curriculum implementation, as well as enriching children’s outdoor play and environmental learning. However, the development of green spaces within school compound is not a priority in Malaysian schools. This paper aims to explore the issues related to the provision of green spaces in Malaysian national primary schools. There are various green spaces that can be provided in school setting such as field, pocket spaces, soft and hard play areas, and animal life, which serves different purposes for children’s activities. Though, the limited budget and the lack of knowledge and design guidelines are among the obstacles encountered by Malaysian schools in developing functional green spaces that provide learning opportunities for children. A greater effort is needed in helping the schools developing their green spaces in terms of funding, expert knowledge and community support.